2016
DOI: 10.1002/ange.201600464
|View full text |Cite
|
Sign up to set email alerts
|

Intrazelluläre Visualisierung der Entstehung von Poly(ADP‐Ribose) mit bioorthogonal funktionalisierten NAD+‐Analoga

Abstract: Poly(ADP-ribos)ylierung (PARylierung) ist eine wichtige posttranslationale Proteinmodifikation und ein bedeutender Signalweg in fast allen Eukaryoten. Grundlegende Prozesse,wie DNA-Reparatur und Transkription, werden von diesem kurzlebigen Polymer und seiner Wechselwirkung mit Proteinen gesteuert. ADP-Ribosyltransferasen (ARTs) erzeugen komplizierte ADP-Riboseketten aus NAD + an diversen Akzeptorproteinen, weshalb die Erforschung der PARylierung auf molekularer Ebene anspruchsvoll ist. Hier präsentieren wir di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…■ RESULTS AND DISCUSSION Design, Synthesis, and Substrate Activity of Bifunctional NAD + . Previous studies have shown that chemical modifications at adenine N6 and C2 positions of NAD + are well tolerated by PARPs, 23,24,27,30,31 and ribose-functionalized NAD + with nicotinamide riboside (NR) 3′-azido displays strong activities for protein PARylation. 37 Thus, we envisioned that covalent attachment of a diazirine photo-cross-linker to adenine N6 or C2 coupled with a 3′-azido NR could generate bifunctional NAD + analogues with significant substrate activities.…”
Section: ■ Introductionmentioning
confidence: 99%
“…■ RESULTS AND DISCUSSION Design, Synthesis, and Substrate Activity of Bifunctional NAD + . Previous studies have shown that chemical modifications at adenine N6 and C2 positions of NAD + are well tolerated by PARPs, 23,24,27,30,31 and ribose-functionalized NAD + with nicotinamide riboside (NR) 3′-azido displays strong activities for protein PARylation. 37 Thus, we envisioned that covalent attachment of a diazirine photo-cross-linker to adenine N6 or C2 coupled with a 3′-azido NR could generate bifunctional NAD + analogues with significant substrate activities.…”
Section: ■ Introductionmentioning
confidence: 99%